Representation of the Collapse of Andalusian Civilization in the Poem Ritsa’ Al-Andalus by Abu Al-Baqa’ Ar-Rundi (1204-1285 AD): A Thematic Study - Hayati , Ana; Shovia,; Nisa’ , Hanun Khiyarotun (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Poetry within the Arabic literary tradition functions not merely as an aesthetic expression but also as a medium for preserving the memory of social dynamics and the historical trajectory of civilizations. One notable poetic work that reflects the collapse of a once-flourishing civilization is Ritsa’ Al-Andalus by Abu Al-Baqa’ Ar-Rundi. Employing a qualitative method with a thematic analysis approach, this study aims to examine the representation of the collapse of Andalusian civilization as depicted in the poem. The findings reveal that the central themes of the poem include the transience of power and civilization, lamentation over the destruction of Islamic territories in Andalusia, transformations in cultural symbols and identity marked by the conversion of mosques into churches, and a historical reflection on the cyclical rise and decline of civilizations. Accordingly, the poem functions not only as a literary elegy but also as a cultural archive that documents historical tragedy while conveying a warning for future generations.